Pangan Lokal Non Beras: Ketahanan Pangan Rumah Tangga pada Era Pandemi Covid-19 di Mentawai - Ade Irwandi; Erwin Erwin (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
Pandemic Covid-19 impact on a human life one of the food. The policy of the pandemic Covid-19 PSBB (large-scale social restrictions) and PPKM (implementation of restrictions on community activities), disturbed and access to food especially at the global level. However, the local food North Pagai have non rice to replace prime food such as rice. By using the method ethnography to uncover and understand and local food commodities and accessibility of households stayed at the pandemic Covid-19.This is done to see food security that relies on local food non rice as an alternative food. The results show food security in the household level can survive by relying on local food that is non rice, taro, bananas and the natural result of the results of the sea and the forest. Local food commodities had grown up in the fields, the garden around shelter. Then, modifying the food of subbet gettek and subbet bagok and tekgi’ consumed dayli. So, even in the pandemic, food security in the household level well remain unfulfilled.